2003
DOI: 10.1523/jneurosci.23-13-05698.2003
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Functional Role of Voltage-Dependent Potassium Channels in Dendrites of Rat Cerebellar Purkinje Neurons

Abstract: We characterized the properties and functional roles of voltage-dependent potassium channels in the dendrites of Purkinje neurons studied in rat cerebellar slices. Using outside-out patches formed Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
128
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(147 citation statements)
references
References 64 publications
(96 reference statements)
16
128
3
Order By: Relevance
“…FSNs, including PCs, require channels with special functional features, such as Kv3 voltage-dependent K + channels (Rudy and McBain, 2001;Akemann and Knopfel, 2006). In agreement with previous studies (Sacco and Tempia, 2002;Martina et al, 2003;McKay and Turner, 2004), we show that PCs express very large voltagedependent and Ca 2+ independent K + currents sensitive to submillimolar doses of TEA. In our study, in order to isolate such currents, we used two independent experimental protocols, which were both effective, as shown by the superimposable results obtained for the voltage dependence of activation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…FSNs, including PCs, require channels with special functional features, such as Kv3 voltage-dependent K + channels (Rudy and McBain, 2001;Akemann and Knopfel, 2006). In agreement with previous studies (Sacco and Tempia, 2002;Martina et al, 2003;McKay and Turner, 2004), we show that PCs express very large voltagedependent and Ca 2+ independent K + currents sensitive to submillimolar doses of TEA. In our study, in order to isolate such currents, we used two independent experimental protocols, which were both effective, as shown by the superimposable results obtained for the voltage dependence of activation.…”
Section: Discussionsupporting
confidence: 91%
“…Our single-cell RT-PCR analysis adds new data to the discussion of a subject where contrasting results have been reported. Regarding Kv3.1, a low but detectable expression was shown by Perney et al (1992) and Weiser et al (1994), while a lack of expression was reported by Weiser et al (1995), Martina et al (2003) and McMahon et al (2004). Regarding Kv3.4, Weiser et al (1994) reported a weak expression by in-situ hybridization, while by immunohistochemistry the results depended on the type of antibody used (Veh et al, 1995;Laube et al, 1996;Martina et al, 2003).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…These channels exhibit relatively fast inactivation as do the Kv1.4, Kv4.1, Kv4.2, and Kv4.3 channels. Kv3.4 expression has been found in the hippocampus, cerebellum, brain stem, spinal cord, skeletal muscle, arterial smooth muscle cells and pancreatic acinar cells (Weiser et al, 1994;Vullhorst et al, 1998;Rudy et al, 1999;Gopel et al, 2000;Abbott et al, 2001;Han et al, 2002;Martina et al, 2003). It performs an important role in modulating electrical excitability of neurons and muscle fibers.…”
Section: Expression Of Kv Channels In Corneal Epithelial Cellsmentioning
confidence: 99%